Surface Velocities of Taylor Glacier, Antarctica - Cuffey, Kurt M.; Bliss, Andrew; Kavanaugh, Jeffrey; Aciego, Sarah (IEDA: US Antarctic Program Data Center, 2007)
Abstract: This data set contains surface velocities of Taylor Glacier, Antarctica, for the year 2003. Measurement period was approximately 12 months. There are approximately 250 locations in this data set.